3D imaging of the human temporal bone by X-ray phase-contrast tomography - Jannis J. Schaeper; Paul Tafforeau; Christoph A. Kampshoff; Carolina Thomas; Alexander Meyer; Christine Stadelmann; M. Charles Liberman; Tobias Moser; Tim Salditt (npj Imaging)
Abstract Studying the subtle and intricate three-dimensional structure of the human cochlea embedded in the temporal bone requires structure-preserving imaging approaches with adaptable field of view and resolution. Synchrotron X-ray phase-contrast tomography at the novel beamline BM18 (EBS, ESRF) offers the unique capability to achieve histological resolution at the scale of the entire organ, based on high lateral coherence, long propagation distances, and optimized spectral range. At the same time advances in laboratory μ-CT instrumentation and protocols also open up new opportunities for 3D micro-anatomy and histopathology, including 3D reconstruction of nerve tissue when suitable staining protocols are used. Here we report on post mortem 3D imaging of human temporal bones and excised human cochleae, both unstained and stained to visualize the auditory nerve. Further, we highlight the use of this imaging modality for development of novel cochlear implant technology.